1990
DOI: 10.1136/thx.45.3.210
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral post-tuberculous lung destruction: the left bronchus syndrome.

Abstract: In a prospective study of 13 patients requiring pneumonectomy for unilateral post-tuberculous lung destruction the left side was found to be affected in 12. Review of a further 172 cases showed the left lung to have been destroyed in 109 (63%). It is suggested that this predominance of the left side is due to the anatomical characteristics of the left main bronchus and that disordered haemodynamics also appear to play a part.Unilateral total post-tuberculous lung destruction is a well recognised cause ofmorbid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 8 publications
1
26
0
1
Order By: Relevance
“…An earlier report (Ashour et al, 1990) revealed that unilateral lung destruction occurred in 10.9% of 1,600 patients with pulmonary tuberculosis in Saudi Arabia. Left sided lung destruction was seen in 64% of those patients.…”
Section: Introductionmentioning
confidence: 97%
“…An earlier report (Ashour et al, 1990) revealed that unilateral lung destruction occurred in 10.9% of 1,600 patients with pulmonary tuberculosis in Saudi Arabia. Left sided lung destruction was seen in 64% of those patients.…”
Section: Introductionmentioning
confidence: 97%
“…The prevalence of NIDDM was also found to be higher than that in the general population reflecting a role of the immune system in clearance of infection [8]. The commoner occurrence of destroyed lung on the left side has been commented on by other workers, and thought to be caused by the poorer drainage created by the hori- zontal left bronchus [9]. Lung destruction was seen even in those patients who had disease for relatively short periods of time perhaps reflecting excessive hypersensitivity.…”
Section: Discussionmentioning
confidence: 94%
“…Bateson in 1976 used the term “destroyed lung” to describe the disease in West Indians and Australian aboriginals 5. TDL occurred almost always in the left lung 7–9, 11, 12…”
Section: Discussionmentioning
confidence: 99%
“…TDL usually occurs as a post‐primary tuberculosis process. The combination of lymph stasis, reduced to absent pulmonary artery flow from bronchial obstruction and infection contribute to the spread of TB infection and eventual lung destruction 12…”
Section: Discussionmentioning
confidence: 99%